The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2020
DOI: 10.17576/gema-2020-2004-03
|View full text |Cite
|
Sign up to set email alerts
|

#WelcomeRefugees: A Critical Discourse Analysis of the Refugee Resettlement Initiative in Canadian News

Abstract: This study focuses on the frames utilized in the depiction of Syrian refugees and social and political actors involved in the Syrian resettlement in Canadian online news media. The role of the media is vital in portraying Syrian refugees' image and affects how the Canadian public perceives them. This paper focuses on utilizing the referential and predicational strategies introduced by the Discourse-Historical Approach (DHA) in framing the Syrian refugees, Liberal government, Conservative party, Canadians, and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 24 publications
0
2
0
Order By: Relevance
“…The refugees are reported as committing domestic violence and sexual assault (Malcolm, 2017). While both of these crimes are serious and require corrective actions, the overt framing bias of the author who uses hyperbolic and sensationalist phrases to generalize isolated events contributes to reinforcing the long-established image of refugees as culturally unadaptable and helps shape the perception of domestic violence and sexual assault as foreign constructs in Canada (Mustafa and Pilus, 2020):…”
Section: Discussionmentioning
confidence: 99%
“…The refugees are reported as committing domestic violence and sexual assault (Malcolm, 2017). While both of these crimes are serious and require corrective actions, the overt framing bias of the author who uses hyperbolic and sensationalist phrases to generalize isolated events contributes to reinforcing the long-established image of refugees as culturally unadaptable and helps shape the perception of domestic violence and sexual assault as foreign constructs in Canada (Mustafa and Pilus, 2020):…”
Section: Discussionmentioning
confidence: 99%
“…The context turns out to be political in its linguistic construct by selecting, emphasizing, and elaborating certain facts while excluding others. For example, Mustafa and Pilus (2020) has shown that National Canadian online news sites have employed the linguistic devices of deixis, metaphor, lexical choices and naming to define the Refugee Resettlement Initiative of the Canadian Govt. both as a success and a failure.…”
Section: Political Discourse Of Covid-19: a Spin Of Convictionmentioning
confidence: 99%